Prevention of Food Borne Diseases through Focused Environmental Sanitation in the Food Market and Abattoir - Afoke , Eunice .N; Nwimo, Ignatius (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2016)
The overwhelming drift to the cities in search of white collar- jobs have greatly increased the economic activities in the market place which in turn results in much waste accumulation without adequate and prompt disposal. Such accumulated refuse dumps in the markets constitute breeding spots for micro-organisms responsible for food borne- diseases such as cholera, typhoid fever and helminthic infections. These diseases account for much morbidity and mortality in developing countries like Nigeria. The paper focused on the need to give the market place, especially the food- markets and abattoirs adequate environmental sanitation attention by all concerned from the policy makers to the market authorities. The paper addressed the concepts of health promotion, food- borne disease and the market place, environmental sanitation in the market place/abattoirs, focused environmental sanitation in the market place progress made in the environmental sanitation in the markets and the challenges in maintaining a healthy food-markets/abattoirs. The paper concluded that if relevant stakeholders should come together with the aim of finding a lasting solution, environmental sanitation problem in the markets/abattoirs would be a thing of the past. It recommended among others that, environmental health unit should be established in the market place to ensure compliance with environmental law; there should be fortnight environmental sanitation. Again, refuse dumps around the market areas and the use of chemicals in food preservation should be banned by the government.